Climate-smart community seed banks conserve and share essential farm biodiversity resources - Kumwenda, Wycliffe; Kadzamira, Mariam A.T.J.; Mungai, Catherine (Technical Centre for Agricultural and Rural Cooperation, 2019)
Community seed banks offer a sustainable way to improve access to high-value seeds, creating viable community-based businesses and maintaining biodiversity. In addition, community seed banks contribute to farmer adaptation. They also indirectly enhance household income diversification, community seed systems, and gender outcomes at community level.